A STUDY ON THE ABILITY OF THE SECOND YEAR STUDENTS OF MTS MUHAMMADIYAH 02 PEKANBARU IN COMPREHENDING DESCRIPTIVE TEXTS - Kurniawan '; Fakhri Ras; Erni ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This descriptive research was aimed to find out the ability of the second year students of MTs Muhammadiyah 02 Pekanbaru in comprehending descriptive texts. The research data were collected in August 2016. The subject of this research was class VIII-2 which consisted of 31 students. The data were collected by giving a test to the students in the form of multiple choice test. The test contained 25 items. Based on the research, it was found out that first: the ability of the second year students in reading comprehension is in the mediocre level with the mean score of 57.38. Second, the students’ mean score in finding the main idea is in good level with the mean score of 78.70, finding the factual information is in good level with the mean score of 65.80, in finding the meaning of vocabulary is in poor level with the mean score of 39.35, in finding references is in mediocre level with the mean score of 44.51, in finding inference is in mediocre level with the mean score of 56.12, in finding generic structure is in mediocre level with the mean score of 60, in finding language features is in mediocre level with the mean score of 60.64. As a conclusion, the highest score obtained by the students is in finding main ideas with the mean score of 78.70 which is categorized into good level, and the lowest score that the students got is in finding the meaning of vocabulary ,with the mean score of 39.35 which is categorized into poor level.Key Words: Study, Ability, Comprehending, Descriptive Texts